2022
DOI: 10.3390/molecules27113561
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Phytochemical-Encapsulated Nanoparticles’ Interaction with Cellular Signalling in the Amelioration of Benign and Malignant Brain Tumours

Abstract: Brain tumours have unresolved challenges that include delay prognosis and lower patient survival rate. The increased understanding of the molecular pathways underlying cancer progression has aided in developing various anticancer medications. Brain cancer is the most malignant and invasive type of cancer, with several subtypes. According to the WHO, they are classified as ependymal tumours, chordomas, gangliocytomas, medulloblastomas, oligodendroglial tumours, diffuse astrocytomas, and other astrocytic tumours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 190 publications
0
3
0
Order By: Relevance
“…[24] To explain these contrasting findings, it should be pointed out that EVs are able to pass through the BBB. [26,27] Thus, there is a possibility that phytochemicals embedded in EVs pass through the BBB to exhibit bioactivities in the brain, an issue currently under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…[24] To explain these contrasting findings, it should be pointed out that EVs are able to pass through the BBB. [26,27] Thus, there is a possibility that phytochemicals embedded in EVs pass through the BBB to exhibit bioactivities in the brain, an issue currently under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in recent years, the combination of plant-derived compounds with nanomaterials has gained enormous popularity. Numerous types of bioactive low-molecular weight metabolites present in plant latex such as alkaloids, flavonoids, have been effectively associated with nanomaterials ( Mehan et al., 2022 ). Several studies revealed that nanoencapsulation of pharmacologically active plant phytochemicals can increase the therapeutic efficiency in cancer treatment ( de Alcantara Lemos et al., 2021 ).…”
Section: Latex-bearing Plants and Nanotechnologymentioning
confidence: 99%
“…Among the natural products, phytochemicals have been modified on the surface of nanomaterials to be utilized as the surface stabilizer and active material. The significant characteristics of phytochemicals are chemical diversity, biological properties, and low toxicity, and it was reported that the combinations of phytochemicals and nanomaterials have been demonstrated to enhance biological activity, biocompatibility, and low toxicity [11][12][13]. Gallic acid (GA), a phytochemical, has excellent potential for antioxidant effects, antiinflammation, and anticancer effects [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%